A humoral stress response in Drosophila. - Ekengren, S.; Tryselius, Y.; Dushay, M.S.; Liu, G.; Steiner, H.; Hultmark, D. (Current Biology, 2001)
The ability to react to unfavorable environmental changes is crucial for survival and reproduction, and several adaptive responses to stress have been conserved during evolution [1-3]. Specific immune and heat shock responses mediate the elimination of invading pathogens and of damaged proteins or cells [4-6]. Furthermore, MAP kinases and other signaling factors mediate cellular responses to a very broad range of environmental insults [7-9]. Here we describe a novel systemic response to stress in Drosophila. The Turandot A (TotA) gene encodes a humoral factor, which is secreted from the fat body and accumulates in the body fluids. TotA is strongly induced upon bacterial challenge, as well as by other types of stress such as high temperature, mechanical pressure, dehydration, UV irradiation, and oxidative agents. It is also upregulated during metamorphosis and at high age. Strikingly, flies that overexpress TotA show prolonged survival and retain normal activity at otherwise lethal temperatures. Although TotA is only induced by severe stress, it responds to a much wider range of stimuli than heat shock genes such as hsp70 or immune genes such as Cecropin A1.